PERAN GURU DALAM MENINGKATKAN MINAT BELAJAR IPA PADA SISWA SEKOLAH DASAR - Audy Mita Amelina; Cindy; Erwin Efendi Hutagalung; Ayatullah Muhammadin Al Fath (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Interest in learning serves as a pivotal psychological driver for achieving scientific literacy in primary education. Despite its importance, empirical evidence suggests that students frequently regard Natural Sciences (IPA) as an intricate and theoretical discipline. This research employs a descriptive qualitative literature review to explore the strategic influence of teachers in enhancing students' engagement with science. The findings underscore that teachers act as critical determinants by assuming multifaceted roles as instructional architects, motivators, facilitators, technological innovators, and evaluators. Through the synergy of these functions, educators can reshape negative student attitudes by fostering inclusive environments and utilizing tangible instructional tools. Ultimately, this study asserts that the professional ingenuity of teachers in delivering pedagogical stimuli is essential for establishing a robust scientific foundation for the next generation.